A short report: parents HPV vaccine knowledge in rural South Florida - Tami L. Thomas; Michelle Caldera; Jeffrey Maurer (Taylor & Francis Group, 2019)
An exploratory pilot descriptive research study was conducted in the rural counties of Hendry and Glades Florida exploring parental knowledge and hesitancy of HPV vaccination. Participants included parents/caregivers with children ages 9 to 13; using quantitative methods, we evaluated knowledge, feelings, and beliefs toward HPV vaccination including vaccination prevalence and correlates among participating parents/caregivers. Our measures included the Parental HPV Survey with a Cronbach's alpha of .96. Hesitancy-focused results revealed 26% of parents showed caution because of stigma around vaccination while attributing low levels of knowledge about HPV vaccination; 80% had a persistent belief HPV vaccination could leave their child sterile, perpetuating hesitancy. Participants with a high-school education or less (64%) and conservative religious affiliation, e.g., Baptist and Catholic (74%), did not decline HPV vaccination. Results are striking considering research indicating conservative religious views and lack of a college education leads to lower HPV vaccination rates. Numerous interventions to increase HPV vaccination have been studied including strong recommendations for increased provider communication but our data indicates increasing public education with community input and a focus on cultural norms in each specific rural community among parents and providers is needed to increase HPV vaccine knowledge and decrease HPV vaccine hesitancy.